Hiding behind culture: Using social defence systems to explore the malaise of the “old guard” in post-apartheid South Africa - Auld, Sharon; Cartwright, Duncan (PINS-Psychology in Society, 2018)
This paper focuses on the experiences of a group of white, Afrikaner, male, former South African Police members who sought psychotherapy during the post-apartheid period. A case study illustrates common themes and explores the applicability of social defence systems theory as a framework for making sense of their symptoms of emotional distress in the wake of threats to their established identity positions. Core findings reflect the painful divergence of psychic and social experiences and the undermining of defensive systems supported by apartheid social values.